Supportive care needs, quality of life and social support among elderly colorectal cancer patients undergoing chemotherapy: a longitudinal study - Lian, Siqin; Hou, Xijie; Liu, Weichen; Li, Ming; Chen, Guolian; Ling, Ying (Frontiers in Oncology, 2024)
Objective The purpose of this study is to examine the changes in supportive care needs, quality of life and social support during different chemotherapy cycles among elderly colorectal cancer patients. Methods This prospective longitudinal study recruited 160 elderly colorectal cancer patients using convenience sampling at a hospital in Guangxi between August 2023 and April 2024. To assess supportive care needs, quality of life, and social support, we used a short form of the Supportive Care Needs Survey (SCNS-SF34), a Functional Assessment of Cancer Therapy-colorectal (FACT-C), and a perceived social support scale (PSSS) prior to chemotherapy, as well as after the first, third, and sixth cycles. Repeated measures analysis of variance was used to validate the changes over time in supportive care needs, quality of life, and social support. Results 155 participants completed all questionnaire sessions across the six cycles. From pre-chemotherapy until after the sixth cycle of chemotherapy, the extent of physical and daily living requirements among all respondents fluctuated between 47.23% and 88.26%, psychological needs ranged from 60.84% to 97.67%, patient care and support needs ranged from 83.75% to 99.35%, healthcare system and information needs varied from 85.98% to 99.00%, while the level of sexual needs decreased from 1.51% to 0.65%. The mean SCNS-SF34 scores for these participants ranged between 103.81 ± 2.28 and 144.10 ± 1.08. Significant increases over time were seen for all domains of SCNS-SF34 (F=126.99, 347.41, 65.00, 72.34, 160.15, p<0.001), keeping a clear upward trend, except for sexual needs(F=0.712, p=0.546). The mean FACT-T scores dropped from 68.80 ± 1.00 to 51.24 ± 1.40, while the mean PSSS scores dropped from 55.77 ± 0.83 to 43.28 ± 1.05. The scores of FACT-T and PSSS showed statistically significant differences (F=231.21, 112.28, p<0.001), maintaining clear downward trends. Conclusion During chemotherapy, elderly colorectal cancer patients continue to require high levels of supportive care, while their quality of life and social support gradually decline. This study offers healthcare practitioners a foundational understanding to identify and address the supportive care needs of elderly colorectal cancer patients across various chemotherapy phases, which facilitates the development of tailored strategies aimed at enhancing patients’ quality of life.